Surgical treatment of a mandibular ameloblastic carcinoma with metastases to the mandibular lymph nodes in a pony. (24th June 2019) - Derham, A. M.; Kushnir, A.; Hoey, S.; Jahns, H.; Hollis, A. R.; Kearney, C. M.
Summary: A 4‐year‐old Connemara filly was presented with a rapidly growing oral mass on the right rostrolateral mandible and a right mandibular lymphadenopathy. Radiographs of the rostral mandible revealed a lytic, infiltrative mass consistent with soft tissue and mineralised material, and displacement of tooth 403. A biopsy showed characteristic histopathological features of an ameloblastic carcinoma. Subsequent FNA of the right abnormally firm and enlarged mandibular lymph node confirmed the metastatic spread. Computed tomography of the head was performed for surgical planning, including sentinel lymph node mapping to rule out other lymph node involvement. An aggressive lesion, consistent with soft tissue of the rostral right mandible was identified with intralesional contrast injection showing drainage of contrast within the right mandibular lymph nodes (Sentinel node). Based on the infiltrative and destructive nature reported in ameloblastic carcinoma in humans, a rostral mandibulectomy was performed, along with complete mandibular lymphadenectomy. The horse recovered uneventfully from surgery. In the early post‐operative period marked lymphoedema of the ventral mandibular region was observed, which resolved 4–5 days post‐operatively. Optimal cosmesis was maintained post‐operatively, and no recurrence has been observed to date – 12 months post‐surgery.